Indicator Analysis of Inclusive Economic Development in Agriculture and Plantation Sector in Indonesia - Mrs Vebtasvili (Fakultas Ekonomi, Universitas Bangka Belitung, 2017)
Sustainable economic development must be achieved by developing countries. Economic development is a major phenomenon in human history placed in the industrial revolutionary movement. Indonesia has made great progress in economic development. Indonesia has an important role in the global economy. The aim of this research is to identify inclusive economic development in agriculture and plantation sectors in Indonesia. This study identifies the agricultural and plantation sectors in the areas of palm oil, rubber, crop and cocoa farming. The results show that agriculture and plantation sector in Indonesia plays an important role in economic development. Production of palm oil, rubber, crop and cocoa farming should be further enhanced in Indonesia, particularly areas that are sufficient for agriculture and plantation cultivation.